IMPLEMENTASI PEMBINAAN TAHSIN QUR’AN DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SISWA/I SMAN 2 KLARI - Tia Febbiyanti; Haerudin; Herdian Kertayasa (LP2M IAIN Sultan Amai Gorontalo, 2026)
Implementation of Qur'an tahsin guidance in improving the Qur'an reading ability of students of SMAN 2 Klari.